Metabolomic and biodirected phytochemical study of Hechtia glomerata, evaluation of its antibacterial and cytotoxic activity, and determination of the mechanism of action of one active compound - Stefani, Tommaso (2020)
Purpose of the study: The pharmaceutical industry has left the active research and development of new antibiotics, and the lack of new molecules caused the antibacterial resistance to become an even more threatening issue. At the same time cancer resistance is also thriving, making old chemotherapeutic drugs useless. Therefore, there is the absolute need of new bioactive molecules to contrast these pathologies. Plants’ natural products have always been a source for bioactive and structurally complex compounds and could represent a solution to these emerging health problems. The majority of the world still relies on the use of ethnomedicine for the treatment and prevention of diseases. This is why in this work a Mexican medicinal plant: Hechtia glomerata Zucc. known as Guapilla was investigated for its curative properties. The goal of this study was to find out the actual antibacterial and cytotoxic activity of this plant’s extracts and its adequacy as source for biologically active compounds. Also, to isolate its major compounds and deeply investigate its secondary metabolites production. Finally, the mechanism of action of one of its bioactive constituents was investigated by microarray assay.